2016
DOI: 10.1080/14659891.2016.1232761
|View full text |Cite
|
Sign up to set email alerts
|

Distress and alcohol-related harms from intimates, friends, and strangers

Abstract: Alcohol’s harms to others (AHTO) has gained increased research and policy attention, yet little information is available on different social relationships involved in such harms or consequences of harms perpetrated by various types of drinkers. Using data from the 2014–15 U.S. National Alcohol Survey (N=5,922), we present analyses comparing frequency and impacts of eight past-year harms from other drinkers. In this sample (53% female; 66% White/Caucasian, 13% Black/African American, and 15% other race; 15% His… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
54
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 32 publications
3
54
1
Order By: Relevance
“…In our study, students of both genders reported harm to be higher from perpetrators outside the family, with strangers being the most common perpetrators. These findings are in variance to other studies which have reported higher rates of harm from known people, with females reporting higher instances of harm by those within the family, and males reporting more harm by those outside their family [17,27,28]. However, the low response rate to the question regarding the relationship to the person 'who has harmed the subject the most because of their drinking' (32.4%) among students who reported harm, limits the robustness of the findings.…”
Section: Discussioncontrasting
confidence: 95%
See 2 more Smart Citations
“…In our study, students of both genders reported harm to be higher from perpetrators outside the family, with strangers being the most common perpetrators. These findings are in variance to other studies which have reported higher rates of harm from known people, with females reporting higher instances of harm by those within the family, and males reporting more harm by those outside their family [17,27,28]. However, the low response rate to the question regarding the relationship to the person 'who has harmed the subject the most because of their drinking' (32.4%) among students who reported harm, limits the robustness of the findings.…”
Section: Discussioncontrasting
confidence: 95%
“…Our finding of students experiencing harm having higher recent psychological distress has been reported earlier . Among students who indicated experiencing various harms in our sample, there was a trend towards students who had experienced physical harm reporting higher distress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each assesses harm from the victim's perspective due to (or attributed to) someone else's drinking during the prior 12 months. Two items assess problems experienced mainly within the family and from intimate others (marital/family problems or financial troubles) (Karriker‐Jaffe and Greenfield, ); 2 assess issues stemming from aggressive drinkers (being pushed, hit or assaulted, or having property vandalized) (Karriker‐Jaffe and Greenfield, ); and the last 2 are attributed to drivers under the influence of alcohol with whom the respondent was a passenger, or who caused a traffic accident (Greenfield et al., ; Karriker‐Jaffe et al., ). All these items were measured for a 12‐month time frame (which technically follows the APS measures of state alcohol policies assessed in the prior year).…”
mentioning
confidence: 99%
“…To date, the AHTO research establishes the prevalence, individual risk factors and mental health consequences for AHTO. Roughly 10% of the US population report AHTO in the past year [8,9], and persons harmed by drinkers in the past year also tend to report higher levels of depression [10,11] and distress [3] as well as lower personal wellbeing [12]. Women [2,[12][13][14][15][16][17], young adults [8,14,[16][17][18][19][20] and persons who belong to minority racial/ethnic groups [21,22] are more likely to report AHTO.…”
Section: Introductionmentioning
confidence: 99%